Two new species of ricinuleids of the genus Pseudocellus (Arachnida: Ricinulei: Ricinoididae) from southern Mexico - Valdez-Mondragón, Alejandro; Francke, Oscar F. (Zootaxa, 2013)
Two new species of ricinuleids of the genus Pseudocellus are described from Mexico: Pseudocellus cruzlopezi sp. nov. from Oaxaca, and Pseudocellus monjarazi sp. nov. from Chiapas. Both species are described from adult males and fe-males. The first species is epigean and edaphomorphic, whereas the second is cavernicolous and troglomorphic. The num-ber of known species of the genus Pseudocellus increases to 25, and Mexican species to 16, indicating that Mexico has the highest diversity of ricinuleids in the world. An updated identification key to adult males of the 16 described species found in Mexico and southern USA is provided.